New feedback functions for synchronizing chaotic maps - M. K. Ali (Discrete Dynamics in Nature and Society, 1998)
Synchronization of chaotic maps is studied using the method of variable feedback. A general method is presented for generating feedback functions for maps. These feedback functions are found very efficient. Our study shows that when the driver and the response systems are fed by common noise, the noise does not affect synchronization. With different but weak noise added to the driver and response systems, approximate synchronization persists.